Co-electrospun-electrosprayed PVA/folic acid nanofibers for transdermal drug delivery: Preparation, characterization, and in vitro cytocompatibility - Parın, Fatma Nur; Aydemir, Ç.İ.; Taner, Gökçe; Yıldırım, Kenan (SAGE Publications Ltd, 2022)
In this study, hydrophilic based bioactive nanofibers were produced via an electrospinning and electrospraying simultaneous process. Poly(vinyl alcohol) (PVA), poly(vinyl alcohol)-gelatin (PVA-Gel), and poly(vinyl alcohol)-alginate (PVA-Alg) polymers were used as the matrix material and folic acid (FA) particles were dispersed simultaneously on the surface of the nanofibers. The morphology of the nanofibers (NFs) was uniform and confirmed by scanning electron microscopy. Thermal behavior, chemical structure of the composite nanofibers were investigated by thermogravimetric analysis, and Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy which showed that no chemical bonding between vitamin and polymers. A fast release of FA-loaded electrospun fibers was carried out by UV-Vis in vitro study within the 8 hour-period in artificial sweat solutions (pH 5.44). The obtained PVA/FA, PVA-Gel/FA, and PVA-Alg/FA fibers released 49.6%, 69.55%, and 50.88% of the sprayed FA in 8 h, indicating the influence of polymer matrix and polymer-drug interactions, on its release from the polymer matrix. Moreover, biocompatibility of all developed novel NFs was assessed by two different cytotoxicity tests, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and neutral red uptake (NRU) assay in L929 (mouse fibroblasts) cell lines. In all cases, it is concluded that these new electrospun fibers had fast-release of the vitamin and the hybrid process is suitable for transdermal patch applications, especially for skin-care products. The results of cytocompatibility assays on L929 reveal that all prepared NFs have no or slight cell toxicity. PVA and PVA-Gel with/without FA nanofibers seems more biocompatible than PVA-Alg nanofibers. © The Author(s) 2021.
Keywords: cytotoxicity; Drug release; electrospinning; electrospraying; folic acid; nanofiber